Usability evaluation of Waze by dyslexic drivers / Marina Saeden - Saeden, Marina (2017)
Mobile phones are nowadays far more than merely devices to communicate with. Especially, smartphones are products that help to make our work and everyday life easier. Along with the advance in technology and popularity of these devices, the use of mobile applications increased enormously in the last years. Based on new techniques like GPS and sensors, like compass and accelerometer, that can determine the orientation of the device, location-based applications coupled with augmented reality views are possible. In the context of this work a usability evaluation of waze by dyslexic drivers is developed. This thesis describes the initial thoughts on usability evaluation this application and the process that led to the findings. The Waze is an adoption of touchscreen interfaces represent a dire turn in the nature of digital game-playing, map editing and technological driving assistance. Dyslexic is classed as a specific learning difficulty.However, the dyslexic diagnosed in individuals who have severe difficulties in learning to read and spell despite having no obvious verbal or non-verbal impairment, sensory deficit, extensive developmental disorder or frank neurological impairment. This research aim is to study the usability evaluation for Waze for dyslexic users.